2020
DOI: 10.3390/jof6030180
|View full text |Cite
|
Sign up to set email alerts
|

Stem Endophytic Mycobiota in Wild and Domesticated Wheat: Structural Differences and Hidden Resources for Wheat Improvement

Abstract: Towards the identification of entophytic fungal taxa with potential for crop improvement, we characterized and compared fungal endophyte communities (FECs) from domesticated bread wheat and two wheat ancestors, Aegilopssharonensis and Triticumdicoccoides. Data generated by next generation sequencing identified a total of 1666 taxa. The FECs in the three plant species contained high proportions of random taxa with low abundance. At plant species level, the majority of abundant taxa were common to all host plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…The domestication of crops, especially wheat, has significantly disrupted the associated microbial community. Fungal endophytes exhibit more diversity and richness in wild wheat cultivars than in cultivated ones ( Sun et al, 2020 ). The D genome of hexapoloid wheat strongly favors Glomeromycetes and Nematoda ( Tkacz et al, 2020 ).…”
Section: The Microbiome Profile Of Wheat Is Spatially and Temporally Dynamicmentioning
confidence: 99%
“…The domestication of crops, especially wheat, has significantly disrupted the associated microbial community. Fungal endophytes exhibit more diversity and richness in wild wheat cultivars than in cultivated ones ( Sun et al, 2020 ). The D genome of hexapoloid wheat strongly favors Glomeromycetes and Nematoda ( Tkacz et al, 2020 ).…”
Section: The Microbiome Profile Of Wheat Is Spatially and Temporally Dynamicmentioning
confidence: 99%
“… Buettner and Noll (2018) found few shared bacterial and archaeal OTUs in their study, indicating that the microbial communities of biogas and sewage-treated plants are distinct in community members and microbial interaction patterns. Sun et al (2020a) illustrated that certain interaction correlations are shared by co-occurrence networks from different sampling sites in wheat and other related cereal plants. Shade and Handelsman (2012) suggested that core taxa should include community members co-varying within a community and shared across communities.…”
Section: Discussionmentioning
confidence: 99%
“…Both domestication and breeding affected network topology, with microbial co-occurrence networks from landraces and tall wheat cultivars being more connected, suggesting a reduced functional redundancy in the root microbiome of modern cultivars. Fungal endophyte communities in wild wheat are richer and more diverse than in cultivated wheat, representing a greater reservoir of potentially beneficial endophytes as a higher proportion of differentially abundant taxa was found [74] . The consequences of plant breeding for the associated microbiome are not yet fully understood, however, it has been proposed that domestication has disrupted selective processes in the assembly of the wheat microbiome [71] .…”
Section: Factors Affecting Wheat Microbiome Structure and Diversitymentioning
confidence: 99%